2009
DOI: 10.1504/ijsom.2009.023235
|View full text |Cite
|
Sign up to set email alerts
|

Service quality monitoring by performance indicators: a proposal for a structured methodology

Abstract: The evaluation of service quality is usually carried out using a suitable set of Performance Indicators (PIs). In general, the development of a proper set of PIs is a fundamental prerequisite to monitor organisation or process performances. Many conceptual models have been proposed in the literature. The question is how to make these models operative. This paper aims to describe a structured methodology to identify a set of PIs for service quality monitoring. First, the service is mapped in order to identify i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…Many methods and tools for measuring service quality and customer satisfaction exist (see also Forsyth 1999 ; Bourne and Neely 2003 ; Franceschini et al 2009 ). In is important to appreciate the interrelationships between service quality and customer satisfaction.…”
Section: Measuring Quality Marketing Performance and Customer Satisfmentioning
confidence: 99%
“…Many methods and tools for measuring service quality and customer satisfaction exist (see also Forsyth 1999 ; Bourne and Neely 2003 ; Franceschini et al 2009 ). In is important to appreciate the interrelationships between service quality and customer satisfaction.…”
Section: Measuring Quality Marketing Performance and Customer Satisfmentioning
confidence: 99%
“…Estos objetivos de representación, definidos básicamente como aspectos o atributos deseables por medio de los cuales se alcanzan unos mejores resultados y que permiten cumplir la estrategia u objetivo central que orienta al proceso, deben ser definidos anticipadamente por la dirección de la empresa (Franceschini, Galetto, & Turina, 2009). …”
Section: El Concepto De Objetivo De Representación Y El Proceso Deunclassified
“…The relationship matrix may be adapted for the development of a PMS (Franceschini et al 2009) as shown in Figure 3b. Rows describe the strategic goals while columns report performance indicators.…”
Section: Building the Relationship Matrixmentioning
confidence: 99%